2019
DOI: 10.1136/bmjopen-2018-024224
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study investigating the underlying motivations of healthy participants in phase I clinical trials

Abstract: ObjectivesIf patients are to reap the benefits of continued drug development, an understanding of why healthy participants take part in phase I clinical trials is imperative. The current study aimed to explore the nature of these underlying motivations which may, in turn, improve the overall participant experience and assist in the development of more effective recruitment and retention strategies.DesignThis study used a qualitative design based on the theory of planned behaviour. Specifically, it explored hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 32 publications
6
37
0
Order By: Relevance
“…In regard to retention, the high adherence of participants in our study was consistent with the study conducted by Ryan and colleagues [20]. It is postulated that the compliance of the older adults in the study was attributable to altruism and convenience of reporting methods [32]. Many older adults reported that they enjoyed participating in these research studies to stay mentally alert and wanted to keep updated on health-related issues.…”
Section: Discussionsupporting
confidence: 86%
“…In regard to retention, the high adherence of participants in our study was consistent with the study conducted by Ryan and colleagues [20]. It is postulated that the compliance of the older adults in the study was attributable to altruism and convenience of reporting methods [32]. Many older adults reported that they enjoyed participating in these research studies to stay mentally alert and wanted to keep updated on health-related issues.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, self-directed dieting for weight loss has been shown to be less effective long-term than HCP supported dieting [ 47 ]. Participants volunteering for clinical trials also tend to be highly motivated to achieve health outcomes and may be incentivised by free healthcare or monitory gifts [ 48 , 49 , 50 ]. Therefore, the results achieved in clinical trials may not reflect those achieved by people seen in real-world clinical settings, and this is a key issue that requires investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to retention, the high adherence of participants in our study was consistent with the study conducted by Ryan and colleagues [ 20 ]. It is postulated that the compliance of the older adults in the study was attributable to altruism and convenience of reporting methods [ 33 ]. Many older adults reported that they enjoyed participating in these research studies to stay mentally alert and wanted to keep updated on health-related issues.…”
Section: Discussionmentioning
confidence: 99%